Spatial Agency in Empowering Vulnerable Communities of Kenya (EAAE Joint Publishings, 2026)
This research aims to investigate and apply a participatory action methodology, focusing on vulnerable communities in Kenya.Learning from various projects implemented in marginalized rural areas, we have developed design frameworks that can make a greater sustainable impact. Our exploration centers around the power of community engagement and participatory mapping, which highlight community knowledge, narratives, and guide the direction of new design interventions. Our ultimate objective is to create inclusive, equitable built environments, with special consideration for the needs of vulnerable populations.Investigating rural Kenyan communities, significant social, economic, and environmental challenges were identified due to remote locations and neglect from government authorities. The absence of support and development plans leaves these areas without the resources to address urgent needs such as healthcare and education. Additionally, the lack of formal land ownership rights and unclear property borders exacerbate the situation and make it increasingly difficult for people to invest in their com-munity, creating an uncertain future.To address these issues, our research and projects propose comprehensive solutions to safeguard community land, establish ownership rights, and reinforce local culture. Participatory mapping and inclusive design methods are employed, involving workshops, interviews, and ongoing monitoring with community members and stakeholders. This approach identifies challenges and cultivates opportunities for collective spatial use and sustainable development.Our projects include the creation of village maps, inclusive public spaces, house prototypes that utilize local resources, and community facilities offering essential programs. The insights gained from these projects act as a catalyst for raising awareness among community leaders, local government officials, and NGOs, with the hope of inspiring similar initiatives in rural contexts worldwide.